Gleichenia-like Korallipteris alineae sp. nov. macrofossils (Polypodiophyta) from the Miocene Landslip Hill silcrete, New Zealand. Issue 3 (3rd July 2017) - Conran, John G.; Jackson, Joseph A.; Lee, Daphne E.; Kennedy, Elizabeth M.
ABSTRACT: Partial fossil frond impressions of a Gleichenia -like fern are described and figured from specimens recovered from the early Miocene Landslip Hill silcrete deposit, Gore Lignite Measures, Southland, New Zealand. The fronds are at least bipinnate, with the pinnae (β costae) bearing opposite pairs of ultimate leaflets; ultimate segments opposite to alternate, laterally directed, ovate, slightly recurved, apices rounded obtuse. The sori are solitary per ultimate segment and there are 5–16 sporangial base scars per sorus. However, because of the difficulty of assigning Gleichenia -like partial fronds to genus, or even to Gleicheniaceae, the fossils are assigned to the fossil fern genus Korallipteris as a new species, K. alineae. Comparison with living and Cenozoic Gleichenia -like macrofossils suggests that the fossil shows morphological resemblance to the extant species G. inclusisora and G. microphylla . The macrofossils are discussed in terms of their possible palaeoenvironmental setting, together with abundant, potentially associated dispersed Gleicheniaceae fossil spores recovered from interbedded lignites. Assuming K. alineae is gleicheniaceous, it probably grew as a pioneer coloniser species in a periodically flooded/disturbed open deltaic riverine environment.